DOES CORPORATE SOCIAL RESPONSIBILITY ENHANCE TRUST AND QUALITY OF WORK LIFE OF WORKERS? - Tho, Nguyen Dinh; Phong, Nguyen Dong; Quan, Tran Ha Minh (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
In recent decades, corporate social responsibility has emerged as a crucial goal in business. Several researchers have agreed that it is a win-win business strategy which contributes to the financial well-being of the firm. However, the question of how corporate social responsibility contributes to the well-being of workers is still unanswered, especially in transitioning markets like Vietnam. Realizing this role of corporate social responsibility in business, this study investigates the impact of corporate social responsibility on both trust in organization and quality of work life of workers in Vietnam. Based on a data set collected from 501 employees working for various firms in Ho Chi Minh City, Vietnam, the study finds that corporate social responsibility directly and indirectly (mediated by trust in organization)enhances quality of work life of workers. The findings of the study suggest that the government and management should pay close attention to corporate social responsibility and make efforts to communicate its corporate social responsibility mission and activities to their employees.